Unconfined Compression Tests on Snow: A Comparative Study. - Kovacs,A; Michitti,F; Kalafut,J (1977)
Results of unconfined compresssion tests performed on snow from Camp Century, Greenland, using a new self-aligning platen system are compared with tests using a more conventional platen system. The average unconfined compressive test strength was 42% higher for samples tested on the new platen assembly vs the old. Test results indicate that the new platen system provides for better sample alignment and therefore a more uniform load distribution applied to the ends of the sample. The higher strength values obtained with the new platen system are considered more representative of the unconfined compressive strength of the snow tested. (Author)